Sequential injection system with modified glass capillary for automation in immunoassay of chondroitin sulfate - Khonyoung S. (2014)
Sequential injection was introduced to perform a multi-step immunoassay. Modified low cost hematocrit glass capillary was employed as the immobilization surface for a competitive immunoassay of chondroitin sulfate (CS), a potential biomarker for cancer. Glass capillary is low cost and adapts well to the flow system without causing back pressure. The analysis time per sample run with automation of the multi-step immunoassay is improved as compared to the conventional batch-wise micro-plate format. The performance of the sequential injection capillary immunoassay (SI-CI) system for CS was evaluated with spiked human serum samples. © Taylor & Francis Group, LLC.